General Relationship between Field Electrical Resistivity Value (ERV) and Basic Geotechnical Properties (BGP) - Zainal Abidin, Mohd Hazreek; Saad, Rosli; Ahmad, Fauziah; Wijeyesekera, Devapriya Chitral; Tajul Baharuddin, Mohamad Faizal (International Journal of Integrated Engineering, 2014)
Electrical resistivity technique is a popular alternative method used in geotechnical soil investigations. Most past applications have been particularly in the area of subsurface ground investigations such as to locate boulder, bedrock, water table, etc. Traditionally, this method was performed by a geophysicist expert for data acquisition, processing and interpretation. The final outcome from the electrical resistivity technique was an anomaly image which used to describe and conclude the particular soil condition measured. The anomalies highlighted uncertainties on the nature of soil that was often variable and depended on each particular site condition that gave a site dependent soil electrical resistivity value (ERV). Hence, this study demonstrates a relationship between ERV (ρ) and some of the basic geotechnical properties (BGP) such as soil moisture content (w), grain size of geomaterial (CS or FS), density (ρbulk and ρdry), porosity (η), void ratio (e) and Atterberg limit (AL). Different soil samples were collected and tested under field and laboratory conditions to determine basic geotechnical properties immediately after the field electrical resistivity method was performed. It was found that the electrical resistivity value was different for number of soils tested and was relatively subjective to variations in the geotechnical properties. In other words, electrical resistivity value was greatly influenced by the geotechnical properties as the ERV was higher due to the lower moisture content, void ratio and porosity with a higher value of soil density and vice versa. The relationship of ERV and BGP can be described by ρ α 1/w, ρ α CS, ρ α 1/FS, ρ α ρbulk/dry and ρ α 1/AL. Hence, it was shown that behaviour of ERV was significantly influenced by the variation of basic soil properties and thus applicable to support and enhance the conventional stand alone anomaly outcome which is traditionally used for interpretation purposes.